Currículo de matemática da Cidade de São Paulo: uma análise do eixo álgebra para o ensino fundamental - Silveira, Tiago Cardoso (2019)
This work aims to analyze the Algebra axis prescribed in the curriculum of the city of São Paulo for High School, in order to verify how this prescription is made and to analyze the learning and development objectives to determine if they contribute to the development of algebraic thinking. Supporting the ideas of this curriculum study, namely, the work of Sacristán (2000) and Pacheco (2005) is used, in order to present the prescribed curriculum. Other researches, such as those of Blanton and Kaput (2005), Lins and Gimenez (2005), Pontes (2006), Canavarro (2007), Ponte, Branco and Matos (2009) and Kieran (1992, 2004, 2011) about this dissertation. This research applies as methodology the documentary analysis, with a qualitative study approach, looking at the City Curriculum (SÃO PAULO, 2017) as the object. As this paper proposes an analysis of the Algebra axis, a cut has been made of this document, so that objects of knowledge and learning and development objectives are studied. The latter are analyzed in the light of Blanton and Kaput (2005) research, which delimits three categories that allow us to look specifically at the development of algebraic thinking: generalized arithmetic, functional thinking and modeling. Thirty-six goals prescribed in the curriculum of the city of São Paulo for the Algebra axis are analyzed, as well as the 21 learning and development objectives present in the articulating axes. As a result of the analysis, it is perceived that the objectives prescribed for Algebra are presented according to the research on the teaching of Algebra in High School, making possible the use of patterns and generalizations in different mathematical contexts and the construction and development of algebraic thinking.